HEGEMONY OF LEGEND LITERATION IN LITERATURE AND THE ENVIRONMENT IN THE DIGITAL ERA (HEGEMONI LITERASI LEGENDA DALAM SASTRA DAN LINGKUNGAN DI ERA DIGITAL) - Khairil Anwar; Zurmailis Zurmailis; Maya Febrianti; Listi Mora Rangkuti; Antonio Costantio Soares (Jurnal Gramatika, 2021)
This research is a study of legends Urang Kayo Hitam in the cities of Jambi, Puti Kacang Mayang di Pekanbaru, and Malin Kundang in Padang in Indonesia. Legend is still alive and has a role in society today, but its existence is nullified by logic because it is considered absurd and out of date. This role can be seen in its hegemony in literature and the environment. This study discusses the hegemony of legends in literature and the local environment. This study is important to show the position and importance of the legend today. This research uses qualitative methods with hegemony theory. The results of the study, found the hegemony of legends in each city literary creativity and the environment. The hegemony is the domination of legends in the creation of various forms and genres of literary works, creation of environmental sites that are vital to people's lives, digital industrial promotion media and services, preservation of values, infrastructure names, and city or place icons.